Relationship Between High Levels of Teacher Preparation and Teacher Turnover and Its Impact on Sustainability of Education Systems in Public Secondary Schools in Bushenyi Ishaka Municipality, Uganda - Tukahirwa Evas Bindeeba; Tukur Muhammad; Lucy Aja; Alex Behakanira Tumwesigye (Journal of Education for Sustainable Development Studies, 2026)
This study examines the relationship between high levels of teacher preparation and teacher turnover in public secondary schools in Bushenyi–Ishaka Municipality, Uganda. Low levels of teacher turnover, which can be achieved through high levels of teacher preparation and support, lead to a more inclusive and equitable quality education and support teacher well-being. This ultimately contributes to a more sustainable and equitable educational environment through reduced disruptions. The study adopted a cross-sectional research design and employed a mixed-methods approach, integrating both quantitative and qualitative techniques within a single study. The target population consisted of 4,454 individuals, from which a sample of 367 respondents was selected using proportionate random sampling based on the number of teachers and students, calculated with Slovin’s formula. Data were collected using questionnaires and interview schedules. Quantitative data were analyzed through Pearson correlation and multiple regression analysis using SPSS software version 27.0. Qualitative data were analyzed through thematic analysis. Reliability was established through Cronbach’s alpha value of 0.872. Data was also analyzed through descriptive statistics like frequencies, means, and percentages. Results showed a strong negative correlation between high levels of preparation (HLP) and teacher turnover (r = -0.878, p < 0.05). This shows that teachers who have high levels of preparation tend to stay in their jobs. Multiple regression analysis was used to determine the influence of motivation on teacher turnover, which was significant at 64.5% (R² = 0.645). These results highlight the critical role of teacher preparation in reducing turnover, as well-prepared teachers tend to be more committed and satisfied with their work. Based on these findings, it is recommended that educational leaders implement comprehensive teacher training programs to enhance preparation and retention, thereby fostering a stable and effective learning environment for students.